Integrating Tat Twam Asi in Language Education: Enhancing Cross–Culture Understanding and Community Interaction in Bali - Putu Niken Praweda Yanti; Wicaksana, GDA; I Gede Budasi; Dewa Putu Ramendra (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
Effective cross-cultural communication is essential in multicultural environments, particularly in regions with high international engagement like Bali. This study explores the integration of the Tat Twam Asi philosophical principle in language education to enhance cultural awareness among German students in an international language program. Tat Twam Asi, meaning